2016
DOI: 10.3390/sports4040051
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation Strategies to Reduce Muscle Damage and Improve Recovery Following Exercise in Females: A Systematic Review

Abstract: Exercise-induced muscle damage (EIMD) caused by unaccustomed or strenuous exercise can result in reduced muscle force, increased muscle soreness, increased intramuscular proteins in the blood, and reduced performance. Pre- and post-exercise optimal nutritional intake is important to assist with muscle-damage repair and reconditioning to allow for an accelerated recovery. The increased demand for training and competing on consecutive days has led to a variety of intervention strategies being used to reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 70 publications
(133 reference statements)
0
7
0
4
Order By: Relevance
“…Common therapeutic interventions that are used to treat the symptoms of EIMD include stretching, massage, electrotherapy, cryotherapy, non-steroidal anti-inflammatory drugs (NSAIDS), as well as nutritional and supplementation strategies [2, 6, 13]. Earlier reviews [12, 1416] have summarized some (but not all) of the widely researched dietary and supplementation strategies that have been examined for their ability to alleviate symptoms of EIMD. In short, Bloomer [14] provided an early review covering the efficacy of antioxidants, β-hydroxy-β-methylbutyrate, as well as several other assorted supplements to reduce the severity of EIMD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common therapeutic interventions that are used to treat the symptoms of EIMD include stretching, massage, electrotherapy, cryotherapy, non-steroidal anti-inflammatory drugs (NSAIDS), as well as nutritional and supplementation strategies [2, 6, 13]. Earlier reviews [12, 1416] have summarized some (but not all) of the widely researched dietary and supplementation strategies that have been examined for their ability to alleviate symptoms of EIMD. In short, Bloomer [14] provided an early review covering the efficacy of antioxidants, β-hydroxy-β-methylbutyrate, as well as several other assorted supplements to reduce the severity of EIMD.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kim and colleagues [15] briefly covered the efficacy of n-3 PUFAs, caffeine, taurine, and dietary polyphenols. Finally, Köhne et al [16] conducted a systematic review and identified five studies that examined the effect of a nutritional intervention on EIMD-related outcomes in female participants. However, none of these studies have comprehensively collated all well-supported or emerging nutritional strategies that are purported to reduce the signs and symptoms of EIMD.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the observed effect may be due to the CHO + PRO group being able to better recover from the training load compared to the CHO group. This is plausible given what is generally known about the benefit of CHO + PRO over CHO alone during recovery that has been elucidated in a review on these effects in females [23]. Relatedly, one study found that participants who consumed CHO + PRO within 2 h post-exercise had better recovery 24 h following an exhaustive bout of cycling than those who consumed an isocaloric CHO beverage in endurance trained males [7].…”
Section: Discussionmentioning
confidence: 95%
“…Participants completed a health history questionnaire, were non-smokers, had no known food allergies and were not taking anti-inflammatory therapies. Females completed a menstrual cycle questionnaire (Köhne et al 2016). Participants abstained from strenuous exercise and alcohol for 48 h prior, and caffeine-containing products on the day of the half-marathon.…”
Section: Participantsmentioning
confidence: 99%